Gas production and rumen fermentation characteristics of buffalo diets containing by-product from some sorghum varieties - Irawan Sugoro; Komang G. Wiryawan; Dewi Apri Astuti; Teguh Wahyono (Jurnal Ilmu Ternak dan Veteriner, 2015)
Sorghum is one of potencial fibre sources as buffalo feed. Quality of sorghum could be increased by irradiation mutation breeding. Samurai 1 and Samurai 2 were products of the irradiation mutation breeding of Pahat. This study was conducted to compare buffalo diets containing Samurai 2 sorghum straw and Samurai 1 bagasse sorghum compared with Pahat sorghum straw using in vitro study. Completely randomized design with 6 treatments and 3 replications was applied in this experiment. The treatment diets were P1 (50% Pahat sorghum straw + 50% concentrate), P2 (50% Pahat sorghum straw silage + 50% concentrate), P3 (50% Samurai 2 sorghum straw + 50% concentrate), P4 (50% Samurai 2 sorghum straw silage + 50% concentrate), P5 (50% Samurai 1 sorghum bagasse + 50% concentrate) and P6 (50% Samurai 1 sorghum bagasse silage + 50% concentrate). The 200 mg DM samples of diets were incubated in 30 ml rumen-buffer fluid for 48 hours. Variables measured were total gas production, CH4 production and rumen fermentation characteristics. Results showed that P2 and P4 produce the highest of gas production (P<0.05) with 60.99 and 60.86 ml/200 mg dry matter respectively. Treatments of P1, P2 and P4 produced the lowest CH4 concentration (P<0.05) with 10.57, 10.90 and 9.82% of total gas, respectively. The P4 produced the highest total volatile fatty acids (VFA), dry matter degradability and organic matter degradability with 109.83 mM, 62.93% and 59.97% respectively, meanwhile ammonia (NH3) concentration was not significantly different. The conclusion showed that straw silage of Samurai 2 was comparable to the Pahat sorghum straw and Samurai 1 bagasse sorghum as buffalo diet. Key Words: Buffalo, CH4 Concentration, Rumen Fermentation Characteristics, Sorghum